2020
DOI: 10.2478/gsr-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microorganisms with an Electronic Nose for Application under Microgravity Conditions

Abstract: AbstractIn this work, we report on the construction, training and functional assessment of an electronic nose (called ‘E-Nose’) that is capable of monitoring the microbial contamination onboard space ships under microgravity conditions. To this end, a commercial electronic nose was modified to allow for the sampling of microbial volatile organic compounds (MVOCs) emitted from relevant bacterial and fungi species. Training of the modified ‘E-Nose’ was performed by establishing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is based on detecting volatile organic compounds (VOCs). It has been successfully used in several biological and agricultural applications [11,12], especially in food spoilage [13][14][15][16][17][18]. Furthermore, it was used for the identification of several bacterial strains and fungi strains, since these microorganisms can produce VOCs during their metabolic activities.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on detecting volatile organic compounds (VOCs). It has been successfully used in several biological and agricultural applications [11,12], especially in food spoilage [13][14][15][16][17][18]. Furthermore, it was used for the identification of several bacterial strains and fungi strains, since these microorganisms can produce VOCs during their metabolic activities.…”
Section: Introductionmentioning
confidence: 99%
“…This allows to transferring identified VOC-fingerprints to learn for other strains of the species (Kunze et al, 2013). It was further found that also the composition of the produced volatiles stays constant during the exponential growth of the microorganisms although the emission of volatiles increases with the number of colony-forming units (CFU) (Reidt et al, 2020). It should critically be noted here that not all studies distinguished precisely between colonization and wound infection.…”
Section: Target Bacteria Vocs and Biofilmsmentioning
confidence: 94%
“…However, MOS sensors are known to have weak precision, are susceptible to poisoning and sensitive to humidity (Karakaya et al, 2020). While the influence of humidity on the sensor performance can be decreased by integration of an independent humidity sensor (Reidt et al, 2020), well-known drift issues and lacking long-term stability still decrease sensor´s ability to provide stable signals over a sufficiently long period (Chai et al, 2022). Such a long-term stability is, however, crucial for long-term data collection to monitor wounds.…”
Section: Metal Oxide Semiconductor (Mos) Sensorsmentioning
confidence: 99%
“…Metal oxide (MOX) gas sensors and sensor arrays, i.e., E-Noses [1], are widely employed in the detection of gases and gas concentrations in the ambient air to aid in a multitude of safety, security, medical, automotive and industrial control scenarios [2][3][4][5][6][7][8][9][10][11][12][13]. All of these applications have been enabled by making progress along the three main directions of research, namely by striving for higher sensitivity, selectivity and stability [14].…”
Section: Introductionmentioning
confidence: 99%